DV-made China : digital subjects and social transformations after independent film - Zhang, Zhen, 1962 July 8-; Zito, Angela (Critical interventions (Honolulu, Hawaii), 2015)
In 1990s post-Reform China, a growing number of people armed with video cameras poured out upon the Chinese landscape to both observe and contribute to the social changes then underway. This digital turn has given us a 'DV China' that includes film and media communities across different social strata and disenfranchised groups. This study takes stock of these phenomena by surveying the social and cultural landscape of grassroots and alternative cinema practices.